Ultrafast ambipolar switching in electrochromic copolymer thin films of zinc(ii) tetrakis(4-aminophenyl)porphyrin-3,4-ethylenedioxythiophene - Kochrekar, Sachin; Sappati, Subrahmanyam; Kumar Jha, Plawan; Mäkilä, Ermei; Jadhav, Ashwini; Damlin, Pia; Salomäki, Mikko; Kvarnström, Carita (Royal Society of Chemistry, 2026)
Electrocopolymerization of different monomers is a useful approach for developing materials with tailored electrochromic properties and expanded color palettes. We report electrocopolymerization of two distinct monomers – zinc(II) tetrakis(4-aminophenyl)porphyrin (ZnTAPP) and 3,4-ethylenedioxythiophene (EDOT) on an FTO-coated glass substrate. Our copolymer, poly(ZnTAPP–EDOT), exhibits a reversible color change from orange-brown to olive-green, with optical contrasts of 25% and 31% in the visible and beginning of the near-IR (bNIR) regions, respectively. It also demonstrates high coloration efficiencies of 434 cm2 C−1 (visible region) and 181 cm2 C−1 (bNIR region). Furthermore, poly(ZnTAPP–EDOT) retains 88%of its electrochromic performance in the visible and 82% in the bNIR regions after 200 redox cycles, along with a fast switching response and strong optical memory under open-circuit conditions. Our time-dependent density functional theory (TDDFT) calculations reveal that the increasing EDOT units between ZnTAPP moieties promote a systematic redshift in absorption peaks and enhance oscillator strengths, attributed to extended π-delocalization facilitated by the added EDOT linkages, corroborating experimental UV-vis data. Our results suggest that the electrocopolymerization of suitable porphyrins with selective monomers can produce electrochromic materials with tunable optical properties, high efficiency, and stability, making them well-suited for use in electrochromic devices.